Perempuan Islam dalam Politik (Analisis Filsafat Ekofeminisme) - Kumari, Fatrawati (Muadalah, 2014)
The Rejection of the Moslems jurists and scholars on womenâs involvement in politics has occurred since the age of classical Islam. Domestication and restrictions on women in the history of Islam has encouraged women to demonstrate their capability in politics. Employing qualitative method and ecofeminism philosophy approach, this study is conducted to answer the question to what extent the success of women in politics. The result of the study shows that the Moslems women have successfully gained a historical recognition for their ability to take significant role in politics both in Islamic world and Indonesia. In addition, the characteristics of Moslems womenâs role in politics turn out to lead to masculinity, which tend to follow the menâs style. Moreover, feminism is an alternative of counterweight to the dominance of masculinity contained in a patriarchal political system.